Development and evaluation of a suicide prevention program for secondary school students - Surachai Chaniang (2019)
© 2019 Pacific Rim International Journal of Nursing Research. All rights reserved. Adolescent suicide is a major public health concern in many countries, including Thailand, and the importance of suicide prevention programs at secondary school level has been recognized. This is the second paper of a large action research study focused on the development, implementation and evaluation of the Thai Suicide Prevention Program for Secondary School Students, undertaken in collaboration with stakeholders of adolescent peer leaders, students, parents, school teachers and administrators. This involved seven steps: 1) establishing mutual commitment and engaging a core working group; 2) conducting a situational analysis; 3) analyzing problems and needs; 4) designing; 5) implementing; 6) evaluating; and 7) critiquing feasibility. Qualitative data were collected from focus group discussions and in-depth interviews and analyzed using content analysis. Quantitative data was collected using suicide knowledge and attitude questionnaires and analyzed using descriptive statistics, and a t-test was used to compare scores preand post-training. The Program outcomes indicated significant positive change in the scores of the three stakeholder groups in suicide knowledge and attitude compared with the baseline scores. Stakeholder reflections noted that adolescent peer leaders developed leadership skills and parents and teachers learnt how to identify at-risk children. The process described illustrates how nurses can work with communities to improve health and build knowledge regarding suicide and prevention programs for adolescents.